Study of the antitumor potential of stauprimide in breast cancer - Carrillo Fernández, Paloma; Téllez Quijorna, Clara; Bernal, Manuel; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Martínez-Póveda, Beatriz Amparo (My University, 2021)
Stauprimide, a semi-synthetic derivative of staurosporine, was characterized in 2009 as a potent differentiation-enhancing compound in embryonic stem cells [1]. Although it was first thought that this compound could maintain the properties of staurosporine as a non-selective inhibitor of protein kinases (especially potent in inhibiting tyrosine kinases), it was found that its potential as an inhibitor of these proteins was not particularly remarkable, ruling out this as its main mechanism of action for the differentiation-enhancing effect. However, a clear effect of stauprimide on embryonic stem cells was identified as an inhibitor of CMYC expression, a key factor in the maintenance of stem cell pluripotency [1]. Given the involvement of CMYC in cancer development, and the effect of stauprimide inhibiting its expression, this compound was proposed as a possible antitumor drug in the treatment of renal cancer [2]. In this work we have studied the in vitro antitumor effect of stauprimide in the context of breast cancer, exploring also the possible mechanisms of action by which stauprimide exerts its effects. The detected activity of this compound on the human adenocarcinoma model used in our studies suggests its potential usefulness in antitumor pharmacological strategies.
Contribución a Congreso (póster)
Keywords: Cáncer - Congresos; Antitumor potential; Breast cancer